Analytic philosophy as a new paradigm of rationalism in the philosophy of the twentieth century - Kulabukhova, Liubov (Actual Problems of Mind, 2017)
The article raises the issues explicating the role and significance of analytic philosophy as one of the most influential rationalistic trends of modern philosophy, as well as linguistic turn as an innovative direction in analytic philosophy, according to which philosophical issues are solved with the most accurate interpretation of speech expressions